Volatiles from the fungal phytopathogen Penicillium aurantiogriseum modulate root metabolism and architecture through proteome resetting - García-Gómez, Pablo; Bahaji, Abdellatif; Gámez-Arcas, Samuel; Muñoz, Francisco José; Sánchez-López, Ángela María; Almagro, Goizeder; Baroja-Fernández, Edurne; Ameztoy, Kinia; De Diego, Nuria; Ugena, Lydia; Spíchal, Lukáš; Doležal, Karel; et al. (Plant, cell & environment, 2020)
Volatile compounds (VCs) emitted by the fungal phytopathogen Penicillium aurantiogriseum promote root growth and developmental changes in Arabidopsis. Here we characterised the metabolic and molecular responses of roots to fungal volatiles. Proteomic analyses revealed that these compounds reduce the levels of aquaporins, the iron carrier IRT1 and apoplastic peroxidases. Fungal VCs also increased the levels of enzymes involved in the production of mevalonate (MVA)-derived isoprenoids, nitrogen assimilation and conversion of methionine to ethylene and cyanide. Consistently, fungal VC-treated roots accumulated high levels of hydrogen peroxide (H2 O2 ), MVA-derived cytokinins, ethylene, cyanide and long-distance nitrogen transport amino acids. qRT-PCR analyses showed that many proteins differentially expressed by fungal VCs are encoded by VC non-responsive genes. Expression patterns of hormone reporters and developmental characterisation of mutants provided evidence for the involvement of cyanide scavenging and enhanced auxin, ethylene, cytokinin and H2 O2 signalling in the root architecture changes promoted by fungal VCs. Our findings show that VCs from P. aurantiogriseum modify root metabolism and architecture, and improve nutrient and water use efficiencies through transcriptionally and non-transcriptionally regulated proteome resetting mechanisms. Some of these mechanisms are subject to long-distance regulation by photosynthesis and differ from those triggered by VCs emitted by beneficial microorganisms.
Keywords: photosynthesis; cyanide scavenging; plant-microbe interaction; Real-Time Polymerase Chain Reaction; Gene Expression Regulation, Plant; Penicillium; growth promotion; Arabidopsis Proteins; Plant Roots; buněčná stěna; biostimulant; fotosyntéza; proteiny huseníčku; kvantitativní polymerázová řetězová reakce; kořeny rostlin; proteomics; Proteome; Photosynthesis; regulace genové exprese u rostlin; hormone signalling; nemoci rostlin; těkavé organické sloučeniny; proteom; microbial volatile compounds; Cell Wall; Arabidopsis; Plant Diseases; Volatile Organic Compounds